Sylloge Nummorum Sasanidarum Tajikistan : Sasanian coins and their imitations from Sogdiana and Tocharistan - Gariboldi, Andrea (Denkschriften (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse) ;, 2017)
This volume presents for the first time within the Sylloge Nummorum Sasanidarum (SNS) series a complete coin hoard. The latter was found in 2007 in the Piran-Shahr region in North-Western Iran, and ranks among the largest and most important hoards ever found on the territory of the Islamic Republic of Iran. Containing altogether 1267 drachms, it provides interesting insights not only into the monetary system of the Late Sasanian period, but also into its economic history, for which only very few sources exist. The publication of this hoard was made possible through the cooperation between the Austrian Academy of Sciences and the Research Institute of ICHTO (Iran Cultural Heritage, Handcrafts and Tourism Organization).